MENGELOLA PENDIDIKAN ISLAM DI ERA MODERN: REFLEKSI DAN LANGKAH STRATEGIS DI PONDOK PASANTREN AZZAKIYYAH - Nurdita Indriawati; Irawan; Rohmat Mulyana Sapdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the integration of philosophical reflection and the application of contemporary management strategies in the management of Islamic education at the Azzakiah Islamic Boarding School in Cileunyi. The study focuses on how Islamic philosophical principles can be used as a conceptual basis in facing the tide of modernization marked by technological developments, globalization, and rapid social dynamics. The research method used is a qualitative approach with a case study design through in-depth interviews, participatory observation, and review of official documents. The results of the study show that although the pesantren has a philosophical orientation based on morals and spirituality, its application in the managerial realm is still limited. Pesantren have begun to adopt modern technology and management methods such as benchmarking and the PDCA cycle, but these applications are not yet fully integrated with Islamic values. Teachers play an important role in shaping the character of santri, although teacher competency development programs are still not well structured. Based on these findings, it is necessary to reconstruct Islamic education management strategies that synergize philosophical reflection with modern management tools so that Islamic educational institutions can be more adaptive to the demands of the times while maintaining their Islamic identity.